Three types of Leishmania mexicana amastigotes: Proteome comparison by quantitative proteomic analysis - Pacakova, Lenka; Harant, Karel; Volf, Petr; Lestinova, Tereza (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania is the unicellular parasite transmitted by phlebotomine sand fly bite. It exists in two different forms; extracellular promastigotes, occurring in the gut of sand flies, and intracellular, round-shaped amastigotes residing mainly in vertebrate macrophages. As amastigotes originating from infected animals are often present in insufficient quality and quantity, two alternative types of amastigotes were introduced for laboratory experiments: axenic amastigotes and amastigotes from macrophages infected in vitro. Nevertheless, there is very little information about the degree of similarity/difference among these three types of amastigotes on proteomic level, whose comparison is crucial for assessing the suitability of using alternative types of amastigotes in experiments. In this study, L. mexicana amastigotes obtained from lesion of infected BALB/c mice were proteomically compared with alternatively cultivated amastigotes (axenic and macrophage-derived ones). Amastigotes of all three types were isolated, individually treated and analysed by LC-MS/MS proteomic analysis with quantification using TMT10-plex isobaric labeling. Significant differences were observed in the abundance of metabolic enzymes, virulence factors and proteins involved in translation and condensation of DNA. The most pronounced differences were observed between axenic amastigotes and lesion-derived amastigotes, macrophage-derived amastigotes were mostly intermediate between axenic and lesion-derived ones.